2009
DOI: 10.1093/annonc/mdn671
|View full text |Cite
|
Sign up to set email alerts
|

Response assessment after an inductive CHOP or CHOP-like regimen with or without rituximab in 103 patients with diffuse large B-cell lymphoma: integrating 18fluorodeoxyglucose positron emission tomography to the International Workshop Criteria

Abstract: The integration of PET in treatment evaluation offers a powerful tool to predict outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 17 publications
5
51
2
Order By: Relevance
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In particular, several studies that have evaluated the role of PET as a prognostic tool during chemotherapy have reported its ability to predict outcomes in aggressive NHL. [5][6][7][8][9][10][11] In force of the pivotal role played by PET in staging, restaging, and response evaluation, the International Workshop Criteria for malignant lymphoma 12 have been revised to incorporate the PET data in NHL outcome assessment, but only at the end of therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PET/CT has become a standard of care in both Hodgkin lymphoma and non-Hodgkin lymphoma as part of the restaging assessment. 38 Patients with a negative PET scan result have an excellent outcome, and multiple studies have shown that FDG-PET performed after treatment is highly predictive of progression-free survival and overall survival in aggressive non-Hodgkin lymphoma [39][40][41][42][43] and follicular lymphoma. 44 PET scans can also be particularly useful in patients with lymphoma who have a residual mass at the completion of therapy.…”
Section: Posttreatment Scans (To Document Remission)mentioning
confidence: 99%
“…complete remission [1]. However, although PET scans are quite sensitive, they are not specific for lymphoma [2][3][4][5][6]. Among the conditions that are also often PET avid and might mimic recurrent lymphoma are other malignancies, sarcoidosis, Wegener's granulomatosis, chronic granulomatous disease, and mycobacterial and aspergillus infections.…”
mentioning
confidence: 99%